2016
DOI: 10.3892/mmr.2016.6026
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum polysaccharides protect fibroblasts against UVB-induced photoaging

Abstract: Ganoderma lucidum has featured in traditional Chinese medicine for >1,000 years. Ganoderma polysaccharides (GL-PS), a major active ingredient in Ganoderma, confer immune regulation, antitumor effects and significant antioxidant effects. The aim of the present study was to investigate the efficacy and mechanism of GL-PS-associated inhibition of ultraviolet B (UVB)-induced photoaging in human fibroblasts in vitro. Primary human skin fibroblasts were cultured, and a fibroblast photoaging model was built through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The total triterpenes in G. lucidum induce apoptosis in MCF-7 cells and attenuate Dimethylbenz[a]anthracene (DMBA) induced mammary and skin carcinomas in experimental animals [ 14 ]. G. lucidum polysaccharides also protect fibroblasts against UVB-induced photoaging [ 15 ]. G. lucidum also showed strong anti-inflammatory activity and it acted as an immunomodulator in inflammation induced by a high-cholesterol diet [ 16 ].…”
Section: Medicinal Properties Of Mushroommentioning
confidence: 99%
“…The total triterpenes in G. lucidum induce apoptosis in MCF-7 cells and attenuate Dimethylbenz[a]anthracene (DMBA) induced mammary and skin carcinomas in experimental animals [ 14 ]. G. lucidum polysaccharides also protect fibroblasts against UVB-induced photoaging [ 15 ]. G. lucidum also showed strong anti-inflammatory activity and it acted as an immunomodulator in inflammation induced by a high-cholesterol diet [ 16 ].…”
Section: Medicinal Properties Of Mushroommentioning
confidence: 99%
“…Modern medical research has shown that G. lucidum contains a variety of compounds with anticancer (Kao et al 2016), hypoglycemic (Yang et al 2018), liver protection (Zhao et al 2019), and anti-inflammatory (Hasnat et al 2015) effects. Studies also suggest that G. lucidum possesses strong antioxidant (Lee et al 2016) antimelanogenesis (Hsu et al 2016), anti-aging (Zeng et al 2017), and skin barrier-repairing (Montalbano 2018) properties. Thus, G. lucidum is important as the lead for the development of pharmaceuticals, nutraceuticals.…”
Section: Physiological Activity Of G Lucidummentioning
confidence: 99%
“…GLPs can inhibit MMP-1 protein expression, promote C-telopeptides of type I collagen protein, and inhibit ROS production in fibroblasts following UVB treatment (Zeng et al 2017).…”
Section: Antioxidant and Anti-aging Activitymentioning
confidence: 99%
“…Ganoderma lucidum (GL), as a famous herbal medicine in China and Japan more than 2000 years, has been prized for its medicinal vitality such as promoting longevity and benefiting for general health [1,2]. Especially, GL polysaccharides (GLPs) are a major bioactive ingredient and has been identified that it has regulatory abilities in most of physiological progress, including antitumor effects, immune modulation, significant antioxidant activity, and hypoglycaemic [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%